2017
DOI: 10.1021/acs.energyfuels.7b00766
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Phase Hydrogenolysis of Glycerol over Highly Active 50%Cu–Zn(8:2)/MgO Catalyst: Reaction Parameter Optimization by Using Response Surface Methodology

Abstract: In this study, a highly promising bimetallic 50%Cu–Zn(8:2)/MgO catalyst was developed for selective hydrogenolysis of glycerol to 1,2-propanediol (1,2-PDO). The catalytic activity was evaluated in a high pressure autoclave reactor. Results demonstrated that the incorporation of Zn into Cu/MgO catalysts enhanced the glycerol conversion and selectivity to 1,2-PDO due to the hydrogen spillover effect. Experimentally maximum glycerol conversion of 98.7% with 94.6% selectivity to 1,2-PDO was achieved at mild reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…[2,[6][7][8] Different supports have been employed, including ZnO, [9][10][11][12][13] Al 2 O 3 , [13][14][15][16] CeO 2 , [17] TiO 2 , [13,14] SiO 2 [13,[18][19][20][21] and some aluminosilicates, [15] ZrO 2 , [13,[22][23][24] and MgO. [13,22,[25][26][27][28] There is a general consensus that bifunctional catalysts with metallic Cu sites as well as (Brønsted and/or Lewis) acidic sites favor the selective formation of propanediols. Thus, the support plays a crucial role in the catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…[2,[6][7][8] Different supports have been employed, including ZnO, [9][10][11][12][13] Al 2 O 3 , [13][14][15][16] CeO 2 , [17] TiO 2 , [13,14] SiO 2 [13,[18][19][20][21] and some aluminosilicates, [15] ZrO 2 , [13,[22][23][24] and MgO. [13,22,[25][26][27][28] There is a general consensus that bifunctional catalysts with metallic Cu sites as well as (Brønsted and/or Lewis) acidic sites favor the selective formation of propanediols. Thus, the support plays a crucial role in the catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research efforts have been devoted to develop active and selective solid catalyst materials with bifunctional natures for both H 2 generation and hydrogenolysis reactions. Pt-based ( Tike and Mahajani, 2006 ; Falcone et al, 2015 ; Feng et al, 2015 ; Von Held Soares et al, 2017 ; Zhang et al, 2020b ; Hu et al, 2020 ; Xia et al, 2020 ; Nie et al, 2021 ; Song et al, 2021 ), Cu-based ( Nie et al, 2021 ; Feng et al, 2015 ; Wang et al, 2015b ; Priya et al, 2016 ; Feng et al, 2011 ; Kant et al, 2017 ; Vasiliadou and Lemonidou, 2013 ; A et al, 2017 ), and Pd-based ( Tike and Mahajani, 2006 ; Feng et al, 2015 ; Mauriello et al, 2015 ; Sun et al, 2017 ; Shafaghat et al, 2019 ; Xia et al, 2020 ; Song et al, 2021 ) catalysts have been proposed and investigated with respect to structure-performance relations. Those studies have confirmed that CTH of glycerol can be achieved under milder temperatures (<200 o C) and pressures (inert <2 MPa), with remarkable atom efficiency for the synthesis of PG as the main product ( Wang et al, 2013 ; Feng et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the inexpensive Cu-based catalysts are highly selective to 1,2-PDO because of their low efficiency toward C-C bond breaking and high selectivity for C-O bond hydro-dehydrogenation [24,25]. Therefore, a variety of supports including Al 2 O 3 , Cr 2 O 3 , MgO, ZnO, ZrO 2 , SiO 2 , C and zeolite have been used in the preparation of Cu-based catalysts and evaluated for glycerol hydrogenolysis [26][27][28]. However, because of their poor thermal stability and pyrophoric nature, the Cu-based catalysts are easily sintered under conditions of high temperature and high hydrogen pressure, which leads to their deactivation [29][30][31].…”
Section: Introductionmentioning
confidence: 99%